THE SCIENTIFIC AND METHODOLOGICAL TRAINING OF THE TEACHING STAFF TO ENSURE THE QUALITY OF MILITARY PROFESSIONAL EDUCATION - Murodova Yorqinoy Tojiyevna, (PEDAGOGS, 2025)
Annotation: This article explores the essential role of scientific and methodological training of teaching staff in ensuring the quality of military professional education. It focuses on the integration of modern pedagogical methodologies, research-based approaches, and practical training techniques to enhance the effectiveness of military education systems. By examining current practices, challenges, and international examples, this study outlines key strategies for improving the quality of instruction and achieving a high standard of military professionalism. The paper emphasizes the importance of continuous professional development for educators in military institutions and the impact it has on the overall performance of military personnel.